Effects of the Application Local Zoledronic Acid On Different Dental Implants in Rats On Osseointegration - Bingul, Muhammet Bahattin; Gul, Mehmet; Dundar, Serkan; Bozoglan, Alihan; Kirtay, Mustafa; Ozupek, Muhammet Fatih; Tasdemir, Ismail (Dove Medical Press Ltd, 2024)
Objective: Recently, a lot of research has been done around the world to popularize the osseointegration of dental implants. In this study, it was investigated the effect of local zoledronic acid application on implants with machined (MAC), resorbable blast materials (RBM), sandblasted and acid-etched (SLA) surface implants integrated in rat tibias. Methodology: A total of 60 female Wistar rats weighing between 270 and 300 g were used in the study. The rats were passing divided into six classes: controls; MAC (n = 10), RBM (n = 10), SLA (n = 10), and local zoledronic acid (LZA) applied groups; LZA-MAC (n = 10), LZA-RBM (n=10) and LZA-SLA (n = 10) and implants were surgically placement into rat tibias in general anesthesia. After a four-week experimental period, the biomechanical bone implant connection level was determined with reverse torque analysis. Results: Osseointegration levels were detected highly in SLA and RBM surface compared with the machined surfaced implants in both control and treatment groups (p < 0.05). Additionally, local application of zoledronic acid in both three groups; implants increased the biomechanic osseointegration level compared with the controls (p < 0.05). Conclusion: In this research, we observe that the local application of the zoledronic acid could increase the osseointegration, and RBM and SLA surface could be better than machined surfaced implants in terms of bone implant connection. In addition, local application of zoledronic acid may be a safer method than systemic application.
Keywords: zoledronic acid; local application; osseointegration; bone implant linkage; bone implant contact; implant plane